Effects of vitamin A supplementation on ovarian development of Astyanax lacustris (Teleostei: Characidae) during the non-breeding season - da Silva, Joseane [UNESP]; Brambila-Souza, Gabriela [UNESP]; Araujo, Daniel de Magalhães; Moreira, Renata G. (Elsevier, 2022)
Vitamin A (VA) is essential for fish reproduction, however, knowledge of VA requirement of broodstock fish is scarce. We investigated the physiological role of VA supplementation in the ovarian maturation of Astyanax lacustris throughout the non-breeding season. Adult females were distributed in five nutritional treatments, which differed by the amount of VA supplemented in a plant-based diet: T1 = 0, T2 = 1800, T3 = 3600, T4 = 7200, and T5 = 14,400 IU kg−1 of VA for 60 days after a period of 16 days feeding on a diet poor in VA to reduce body VA content. Plasma total lipids (TL), lipoproteins, and 17β-estradiol (E2) levels were measured after 30 and 60 days. Somatic indexes and morphophysiological ovarian parameters were calculated and VA concentration was analyzed in the ovaries and liver after 60 days. VA supplementation did not increase the concentration of this nutrient in the liver and ovaries. E2 plasma level increased in animals fed on 3600 IU kg−1 of VA (T3) after 60 days and females from T5 group presented a higher RF after 60 days. Ovarian development increased after 60 days compared to that after 30 days, confirmed by the higher gonadosomatic index (all groups). The supplementation with the highest VA level increased RF and decreased plasma TL (after 30 days) and low-density lipoprotein (LDL) (after 60 days) concentrations, showing a potential to improve reproduction even during the non-breeding season; however, its nutritional requirements of VA could be higher.
Keywords: Broodstock nutrition; Estradiol; Lipoproteins; Ovarian morphology; Reproduction